Evaluation of growth of Chlorella ellipsoidea in different culture media - Jahan, F; Rahman, MS; Hossain, MA (International Journal of Agricultural Research, Innovation and Technology, 2015)
An experiment was conducted to evaluate the growth of Chlorella ellipsoidea in three different media viz,. medium I (pulse bran), medium II (soil extract) and medium III (inorganic) under the natural environmental conditions. The alga, C. ellipsoidea, reached maximum cell density of 56.32 × 106 cells ml-1 in 10 days in medium I (pulse bran), maximum cell density of 102.99 × 106 cells ml-1 in 11 days in medium II (soil extract) and maximum cell density of 64.23 × 106 cells ml-1 in 12 days in medium III (inorganic medium). The ranges of water temperature, air temperature and light intensity were 22 to 32ºC, 22 to 34ºC and 2.11 to 4.31 (× 103) lux, respectively during the culture period. The average sunshine period was 7.65 ± 1.57 hours. Total alkalinity, free CO2, pH, NO3-N, PO4- P of algal culture medium I, medium II and medium III were 220, 200 and 150 mg L-1 ; 26, 9 and 19 mg L-1; 7.9, 7.6 and 7.5; 45, 45 and 133.33 mg L-1; 10.9, 15.1 and 37.06 mg L-1, respectively. Cell densities of cultures of C. ellipsoidea under three treatments I, II and III, it can be concluded that cell densities under 3 treatments are significantly different (F=39.78) and treatment II (soil extract medium) is the best for algal (C. ellipsoidea) culture among three treatments. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22636 Int. J. Agril. Res. Innov. & Tech. 4 (2): 6-10, December, 2014